Hybrid Metaheuristics 8th International Workshop, HM 2013, Ischia, Italy, May 23-25, 2013. Proceedings - Blesa, Maria J.; Blum, Christian; Festa, Paola; Roli, Andrea; Sampels, Michael (Theoretical Computer Science and General Issues, 2013)
This book constitutes the refereed proceedings of the 8th International Workshop on Hybrid Metaheuristics, HM 2013, held in Ischia, Italy, in May 2013. The 16 revised full papers presented were carefully reviewed and selected from 30 submissions. The selected papers cover both theoretical and experimental results, including new paradigmatic hybrid solvers and automatic design approaches as well as applications to logistics and public transport.